2018
DOI: 10.1111/jdi.12803
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐ribonucleic acid‐binding site variants of type 2 diabetes candidate loci predispose to gestational diabetes mellitus in Chinese Han women

Abstract: Aims/IntroductionEmerging evidence has suggested that the genetic background of gestational diabetes mellitus (GDM) was analogous to type 2 diabetes mellitus. In contrast to type 2 diabetes mellitus, the genetic studies for GDM were limited. Accordingly, the aim of the present study was to extensively explore the influence of micro‐ribonucleic acid‐binding single‐nucleotide polymorphisms (SNPs) in type 2 diabetes mellitus candidate loci on GDM susceptibility in Chinese.Materials and MethodsA total of 839 GDM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Notwithstanding, during pregnancy the percentage of β-cells expressing PAX4 transiently increases correlating with a higher proliferation of β-cells, highlighting the role of this transcription factor in the adaptation processes that take place during gestation to compensate for the increased insulin resistance [86]. In agreement with this, recent studies have associated SNPs near or within the PAX4 gene with GDM [96,97]. Based on the importance of PAX4 on β-cell formation and plasticity, we can presume that women harboring detrimental mutations in this transcription factor will likely have a reduced β-cell mass with a blunted adaptive response to the increase in insulin resistance, rendering these women more susceptible to develop GDM.…”
Section: Pax4 a Master Regulator Of β-Cell Phenotype And Plasticity mentioning
confidence: 65%
“…Notwithstanding, during pregnancy the percentage of β-cells expressing PAX4 transiently increases correlating with a higher proliferation of β-cells, highlighting the role of this transcription factor in the adaptation processes that take place during gestation to compensate for the increased insulin resistance [86]. In agreement with this, recent studies have associated SNPs near or within the PAX4 gene with GDM [96,97]. Based on the importance of PAX4 on β-cell formation and plasticity, we can presume that women harboring detrimental mutations in this transcription factor will likely have a reduced β-cell mass with a blunted adaptive response to the increase in insulin resistance, rendering these women more susceptible to develop GDM.…”
Section: Pax4 a Master Regulator Of β-Cell Phenotype And Plasticity mentioning
confidence: 65%
“…In support of this suggestion, Wang et al (33) indicated that miR-binding-single nucleotide polymorphisms in T2DM candidate loci were associated with GDM susceptibility and supposed that a similar genetic basis for GDM and T2DM.…”
Section: Discussion:-mentioning
confidence: 94%
“…The observation that the adaptor AP1 and retromer play opposing roles in trafficking of sortilin between the Golgi apparatus and lysosomes was one of the first hints that retromer could function in trafficking pathways germane to GLUT4 [55]. The retromer subunit Vps26 is associated with T2DM in South Asian populations [56], and genome-wide association and other studies have further piqued interest in retromer in the context of diabetes [57,58]. Using a human adipocyte cell line, Yang et al showed that retromer components Vps26, Vps35, and SNX27 colocalise with intracellular GLUT4 and exhibit insulin-dependent translocation to the PM [59].…”
Section: Trends Trends In In Cell Biology Cell Biologymentioning
confidence: 99%